The virtual reality Walking Corsi Test. (July 2015) - Nori, Raffaella; Piccardi, Laura; Migliori, Matteo; Guidazzoli, Antonella; Frasca, Francesca; De Luca, Daniele; Giusberti, Fiorella
Highlights: The WalCT virtual reality test was developed to assess topographical memory. Studying the presence of gender-related differences in the virtual or real WalCT. The people's performance in virtual and real WalCT did not differ. Men outperformed women both in real and virtual WalCT. Gender differences are explained as VSWM load needed to complete the tasks. Abstract: We compared the performance of men and women on a modified and a virtual version of the Walking Corsi Test (WalCT). The WalCT is a large version of the Corsi Block-Tapping Task that requires learning a path and then recalling it. It has been proved to measure topographical memory. The main aim of the study was to compare the effects of real and virtual reality learning environment on the acquisition of spatial information. A secondary aim was to detect the presence of gender-related differences in the two environments. Specifically, we expected that men would perform better in both environments. Eighty college students (40 men) were assigned to real or virtual environments and had to learn four different paths. Gender differences emerged in both environments: men outperformed women in both the real and the virtual reality environment. Results did not show difference in virtual and real environment supporting the equivalence of the two tests to measure topographical memory. Gender-related differences are interpreted in light of Coluccia and Louse's model, according to which men outperform women when tasks require a high visuo-spatial working memory load and the different spatial strategy used by men and women.